PENGARUH HARGA, PRODUK, IKLAN, TEMPAT DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MIE INSTANT MEREK INDOMIE - louis bopeng (Cakrawala Management Business Journal, 2020)
The research objective is to determine the effect of price, product, advertisement, place and brand image variables partially and simultaneously influencing the indomie brand instant noodle purchase decision. This type of associative research with quantitative data and data sources includes primary data and secondary data. Non probability sampling method and sampling technique using accidental sampling. The data analysis technique used multiple linear regression analysis, classic assumption test, R2, t test, F test. The results showed that the price and advertising variables partially had no effect on purchasing decisions. Evidenced by the t value of the price and advertising is -1.341 and -, 512 with a significance level of 0.184 and 0.610 where the significance value is greater than 0.05 (0.184 and 0.610> 0.05). The results of this study indicate that product, place and brand image variables partially influence purchasing decisions. Simultaneous test results indicate that there are effects of price, product, advertisement, place and brand image variables on purchasing decisions.